Effect of neridronate on axial involvement in patients with spondyloarthritis when biologics are not possible. Results of a monocentric study - Crotti, Chiara; Di Taranto, Raffaele; Orsini, Francesco; Ferrito, Matteo; Varenna, Massimo; Favalli, Ennio Giulio; Caporali, Roberto (Frontiers in Medicine, 2023)
Introduction This study aims to examine the potential effectiveness of intravenous neridronate (IVNer) on axial involvement in patients with spondyloarthritis (SpA) refractory to non-steroidal anti-inflammatory drugs (NSAIDs) but not eligible for biological disease-modifying antirheumatic drugs (bDMARDs). Method Patients with active SpA (BASDAI score ≥ 4) and active sacroiliitis (SI) on MRI (according to ASAS MRI definition), who were NSAID-insufficient responder/intolerant but not eligible for bDMARDs, were retrospectively recruited in a tertiary rheumatology centre between September 2015 and December 2021. IVNer (100 mg) was administered to the patients on days 1, 4, 7, and 10. Responses were evaluated 60 days after the last infusion as the median changes from the baseline of BASDAI and Visual Analogue Scale (VAS) pain and there are improvements on MRI signs. Results A total of 38 patients (26 axial SpA, 3 enteropathic arthritis, and 9 axial psoriatic arthritis) were included [66% women, mean age ± SD: 38.0 ± 14.1 years, mean disease duration: 30.5 ± 49.5 months (range 1.0–298), 47% HLAB27+]. The reason for bDMARD ineligibility was concurrent solid tumors (n = 6) or hematological (n = 1) malignancy, comorbidities (n = 11), or patient preference (n = 20). Both median BASDAI [5.83 (4.2–8.33) versus 3.66 (1.1–6.85), p < 0.001] and VAS pain [7 (5.75–8.0) versus 3 (1.0–7.0), p < 0.0001] significantly decreased after IVNer. Of 28 available MRI at follow-up, we observed a complete (36%) or partial (39%) resolution of sacroiliitis or a persistent activity (25%). Discussion IVNer was effective in improving axial involvement in patients with SpA refractory to NSAIDs but not eligible for bDMARDs. IVNer can be considered as a potential alternative therapeutic option in selected settings.